2018
DOI: 10.1016/j.jchromb.2018.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Human skin volatiles: Passive sampling and GC × GC-ToFMS analysis as a tool to investigate the skin microbiome and interactions with anthropophilic mosquito disease vectors

Abstract: Volatile organic compounds (VOCs) emanating from the surfaces of human skin are of great interest to researchers in medical and forensic fields, as well as to biologists studying the ecology of blood-feeding insect vectors of human disease. Research involving the comparison of relative abundances of VOCs emanating from human skin is currently limited by the methodology used for sample collection and pre-concentration. The use of in-house developed silicone rubber (polydimethylsiloxane (PDMS)) passive sampling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 76 publications
(51 reference statements)
1
39
0
Order By: Relevance
“…The BFR-PAR (Brominated Flame Retardant -native compounds stock solution) mixture [including 10,15,17,28,30,47,49,66,71,77,85,99,100,119,126,[138][139][140]153,154,156,169,180,183,184,191,196,197,201,[203][204][205][206][207][208][209], pentabromoethyl benzene (PBEB), hexabromobenzene (HBB), 1,2-bis(2,4,6-tribromophenoxy)ethane (TBE), and decabromodiphenyl ethane (DBDPE)], BDE-MXE (Brominated Diphenyl Ether -native solution mixture) solution mixture 15,17,28,49,47,66,71,85,99,100,119,126,138,153,154,156,169,184,183,191,196,197,206,207,…”
Section: Standardsmentioning
confidence: 99%
See 1 more Smart Citation
“…The BFR-PAR (Brominated Flame Retardant -native compounds stock solution) mixture [including 10,15,17,28,30,47,49,66,71,77,85,99,100,119,126,[138][139][140]153,154,156,169,180,183,184,191,196,197,201,[203][204][205][206][207][208][209], pentabromoethyl benzene (PBEB), hexabromobenzene (HBB), 1,2-bis(2,4,6-tribromophenoxy)ethane (TBE), and decabromodiphenyl ethane (DBDPE)], BDE-MXE (Brominated Diphenyl Ether -native solution mixture) solution mixture 15,17,28,49,47,66,71,85,99,100,119,126,138,153,154,156,169,184,183,191,196,197,206,207,…”
Section: Standardsmentioning
confidence: 99%
“…As passive samplers, silicone wristbands work by chemical diffusion (absorption) of an environmental contaminant into the polymer of the silicone over time [4]. They were first introduced by O'Connell et al [5] in 2014 to assess exposure in an occupational setting, but have since been used in several studies, ranging from assessment of pesticide exposure among farmers in West Africa [6] and Peru [7] and flame retardant exposure among preschool children in the United States [4,8,9], to assessment of volatile organic chemicals emanating from the surface of human skin [10]. These studies have demonstrated that a commercial silicone wristband, worn by study participants, offers a non-invasive and simple way to quantify personal exposure to multiple chemicals from multiple microenvironments and within a multiday time period.…”
Section: Introductionmentioning
confidence: 99%
“…glass beads, cotton gauze, polydimethylsiloxane membranes) [12], [36], [37]. More recently, polydimethylsiloxane tubing has been employed as a wearable passive sampler looped around the wrist or ankle [38]. Volatiles can be recovered from these phases for subsequent analysis via thermal desorption, solvent extraction, or collection onto an adsorbent trap (e.g.…”
Section: Sampling and Analysis Of Skin Volatile Emissionsmentioning
confidence: 99%
“…Unconventional headspace extractive samplers including PDMS tubing sampling loops and silicone wristbands have been suggested in several studies for qualitative monitoring purposes. For instance, Roodt et al used PDMS tubing in a study investigating the relationship between skin microbiome and anthropophilic mosquito disease vectors [77]. PDMS tubing was cut (180 and 240 mm tubing length, 0.25 mm inner diameter) to manufacture sampler loops (Figure 5b).…”
Section: Other Wearable Headspace Extractive Samplersmentioning
confidence: 99%
“…(b) Wrist (left) and ankle (right) sampling using a PDMS loop passive sampling device. (c) c.1-2 bags used for transport that were attached to track participant ID and exposure time in the occupational deployments; c.3 single wristband deployment.Reproduced from[75,77,78], with permission from Elsevier and ACS Publishing, 2019.…”
mentioning
confidence: 99%